2012
DOI: 10.1182/blood-2010-11-314781
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme (CD143) specifies emerging lympho-hematopoietic progenitors in the human embryo

Abstract: Adult-type lympho-myeloid hematopoietic progenitors are first generated in the aorta-gonad-mesonephros region between days 27 and 40 of human embryonic development, but an elusive blood forming potential is present earlier in the underlying splanchnopleura. In the present study, we show that angiotensinconverting enzyme (ACE, also known as CD143), a recently identified cell-surface marker of adult human hematopoietic stem cells, is already expressed in all presumptive and developing bloodforming tissues of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
76
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(94 citation statements)
references
References 50 publications
11
76
0
1
Order By: Relevance
“…Remarkably, ACE is a marker identifying these early progenitors (Jokubaitis et al, 2008;Tavian et al, 2010). ACE + cells sorted from the splanchnopleura generated colonies of hematopoietic cells over 40 times more frequently than ACE -cells (Sinka et al, 2012). ACE therefore appears as the earliest marker of prehematopoietic mesoderm inside the human embryo, and these ACE + CD34…”
Section: F Early Hematopoiesismentioning
confidence: 99%
“…Remarkably, ACE is a marker identifying these early progenitors (Jokubaitis et al, 2008;Tavian et al, 2010). ACE + cells sorted from the splanchnopleura generated colonies of hematopoietic cells over 40 times more frequently than ACE -cells (Sinka et al, 2012). ACE therefore appears as the earliest marker of prehematopoietic mesoderm inside the human embryo, and these ACE + CD34…”
Section: F Early Hematopoiesismentioning
confidence: 99%
“…These findings indicate that RENIN is an active molecule for both myeloid and lymphoid neoplastic disorders. ACE existence throughout hematopoietic ontogeny 7,8 indicates primitive hematopoiesis casts attention on the effects of RAS on neoplastic tissues. Immunohistochemical studies have shown the possible role of ACE/RAS in BM by evaluating ACE expression in normal BM, several myeloproliferative disorders and myelodysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,6 Local RAS is effective even at the stage of primitive embryonic hematopoiesis. 7,8 There is preliminary evidence that local BM RAS could affect neoplastic hematopoiesis. [9][10][11][12][13][14][15][16] Over-expression of the angiotensin-converting enzyme (ACE) (CD 143) surface antigen in leukemic myeloid blast cells have been detected by flow cytometric analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Expression of angiotensin converting enzyme (ACE), which labels human foetal liver HSCs (Jokubaitis et al, 2008), identifies scattered ACE + CD34 − cells beneath the dorsal aorta (Sinka et al, 2012). These have been postulated to represent IAHC precursors, which upregulate CD34 and after integration into the CD34 + endothelial lining form ACE + CD34 + IAHCs (Sinka et al, 2012). Identification of the exact migration pathways during HSC specification in the mammalian AGM region remains one of the least explored issues in the field.…”
Section: The Agm Regionmentioning
confidence: 99%
“…This could reflect a number of scenarios, including 'excessive' endothelial-to-haematopoietic transition (EHT) activity in situ, transendothelial cell migration towards the aortic lumen into the bloodstream (Bertrand et al, 2005;Rybtsov et al, 2011), or migration of EHT-undergoing cells in the opposite direction, towards the venous system, as described in zebrafish (Bertrand et al, 2010;Kissa and Herbomel, 2010). Expression of angiotensin converting enzyme (ACE), which labels human foetal liver HSCs (Jokubaitis et al, 2008), identifies scattered ACE + CD34 − cells beneath the dorsal aorta (Sinka et al, 2012). These have been postulated to represent IAHC precursors, which upregulate CD34 and after integration into the CD34 + endothelial lining form ACE + CD34 + IAHCs (Sinka et al, 2012).…”
Section: The Agm Regionmentioning
confidence: 99%